2009
DOI: 10.1016/j.rmed.2008.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Duration of pulmonary rehabilitation to achieve a plateau in quality of life and walk test in COPD

Abstract: A program of 3 weekly 3-h sessions of outpatient pulmonary rehabilitation program should last at least 8 weeks in order to achieve optimal HRQL and exercise tolerance for most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 32 publications
(24 reference statements)
1
14
0
2
Order By: Relevance
“…Previous studies using the 6MWT were conducted in patients with COPD, but did not include healthy subjects 13,14…”
mentioning
confidence: 99%
“…Previous studies using the 6MWT were conducted in patients with COPD, but did not include healthy subjects 13,14…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] These mechanisms have the potential to alter inputs into the perceptual processes for the sensation of breathlessness. 9,49 The greatest mean improvements in the 6MWD were for subjects no longer volunteering descriptors of air hunger (increase of 46 m) or work/effort (increase of 47 m, see Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Exercise of sufficient duration and intensity is associated with reduction in skeletal muscle dysfunction, may enhance mechanical efficiency of physical activities, and may reduce or delay the onset of dynamic hyperinflation during exercise and reduce sensitivity to dyspnea. [1][2][3][4][5][6][7] While participation in CPRP has been shown to reduce the intensity of dyspnea and impact of dyspnea on health related quality of life, 2 whether participation in CPRP moderates the qualitative sensation of dyspnea is less clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Green et al [79] concluded that for patients recruited from the same centre, those undertaking a seven week training programme had better health outcomes than a group who undertook a 4 week programme. Solanes et al [80] claimed that a minimum of 8 weeks of rehabilitation (with three sessions per week) is necessary for improvements in health outcomes to be observed. [86] suggested that other reasons include not feeling comfortable in taking part in group activities, not feeling safe with health professionals who are conducting rehabilitation programmes, and personal beliefs or experiences about their illness.…”
Section: Duration Of a Pr Programmementioning
confidence: 99%